Plan de exportación para el proceso documentario de la asociación Urocal en la provincia de El Oro - Romero Alvarez, Maryury del Pilar (2015)
The purpose of this report the case study is to increase knowledge about export plans to identify opportunities and competitiveness with companies in the international market, it is important to prepare this plan to identify and select the market and that companies Exporting to present and promote their products, considering the diversification of customers to protect their trade balance imbalance and minimize risks and optimize operating results. Besides data on the requirements involved in the documentary process in the case of organic products is conceptualized. In the report the process of diagnosis, treatment literature, analysis of context and development of the matrix of requirements in this case of the Regional Union of peasant organizations coastal UROCAL described, with emphasis on international trade in the province of El Oro . Exporting companies should design and plan export opportunity for the effectiveness of transporting their products and positioning in the international market. The purpose is that it meets the standards required documentary export to be enrolled in an entity responsible for control and granting of approval by the timely delivery of documents. It arises the need to engage in the global market by globalization of the economy, also to seek profitability in all international markets for the company to ensure a long-term, lower risk of being in a single market and take advantage expanded market opportunities through trade agreements.